Analisis Permintaan Impor Barang Modal di Indonesia - Rizka Novianty Haninda; Nur Hami (Fakultas Ekonomi Universitas Yos Soedarso, 2021)
The purposes of this study to analyze the influence of the import demand of capital goods in Indonesia with independent variables national income, kurs, inflation, and foreign rates interest. This study uses time series data for 2004:Q1- 2020:Q4 period, using multiple regression with error correction model (ECM) method. The result of the study shows that the national income has positive effect, kurs has negative effect, inflation has positive effect but not significant and foreign rate interest not effect the demand imports of capital goods in Indonesia. Keyword : Import of Capital Goods; National Income; Kurs; Inflation; and Foreign Rate Interest.